Thermal Modeling of an Integrated Circular Inductor - Y. Benhadda; A. Hamid; T. Lebey (Журнал нано- та електронної фізики)
We present in this paper a study on the thermal behavior of an integrated circular inductor. We determinate a mathematical expression giving the evolution of temperatures in an integrated inductor using the separation of variables method and a visualization of the thermal behavior is determined in 3D space dimension using the finite element method.